Impact of Brain Gym® on health outcomes of toddlers born with low birth weight: a randomized trial - Setiawan, Cahyo; Kartini, Apoina; Winarni, Sri; Darundiati, Yusniar Hanani (Paediatrica Indonesiana, 2025)
Background Low birth weight (LBW) children are at risk of developmental delay, including impaired motor skills, cognitive function, and stress regulation. Brain Gym® activities have been shown to improve motor coordination, attention span, and fine motor skills in preschool and primary school-aged children. Evidence for the use of Brain Gym® is limited for infants and toddlers with medical vulnerabilities such as low birth weight (LBW), who are at increased risk of developmental delay and heightened stress sensitivity. Objective To evaluate the impact of Brain Gym® exercises on cognitive function, motor skills (fine and gross motor), and cortisol levels in children aged 12–23 months with a history of LBW compared to a control group. Methods  A randomized controlled trial (RCT) was conducted in Sragen, Indonesia, involving 80 low birth weight (LBW) children aged 12 to 23 months. Participants were randomly allocated into two groups: an experimental group receiving Brain Gym® intervention and a control group.The experimental group received Brain Gym® exercises combined with routine baby massage, while the control group received only baby massage. Cognitive and motor development were assessed using the Denver Developmental Screening Test (DDST), while stress biomarkers were measured through salivary cortisol levels using enzyme-linked immunosorbent assay (ELISA). Assessments were conducted at baseline (pre-intervention) and after the 8-week intervention period. The evaluators who administered the DDST and laboratory staff analyzing cortisol were blinded to group allocation. Results The primary outcomes of this study were motor skills, cortisol levels, and cognitive function. At baseline, there were no significant differences between the Brain Gym® group and the control group in fine motor, gross motor, or cognitive function scores, as assessed by the DDST. After the intervention, between-group comparisons revealed no statistically significant differences in gross motor, fine motor, cortisol, or cognitive function outcomes. Within-group analysis showed that gross motor scores in the Brain Gym® group significantly increased after the intervention (P = 0.038), while fine motor scores demonstrated a non-significant trend toward improvement (P = 0.110). Cortisol levels in the Brain Gym® group significantly decreased (P = 0.009), whereas the control group exhibited no significant changes in gross motor (P = 0.548), fine motor, or cortisol levels (P = 0.118). Cognitive function scores remained statistically unchanged in both groups. Conclusion Our findings suggest that Brain Gym® exercises can improve gross motor function and reduce stress in LBW children. These findings highlight the potential of early interventions in enhancing development, but should be interpreted cautiously due to the modest sample size and short intervention period. Future studies should focus on the long-term effects and the mechanisms underlying these improvements.